Impact on Holistic Learning of the Extension Project “Grandfather and Grandmother: Tales of Yesterday - Catipay, Trina Marie A.; Largo, Rowena C; Alvarado, Elsie T; Bacalla, Lita A; Gaihe, Mae Ann Q (Eximia, 2025)
Abstract. The Filipino family is an image of a deep appreciation for Philippine culture. This impact study aims to assess and provide a broader understanding of how to further strengthen the emotional, mental, physical, and social aspects of life for the elderly at the Seven Sisters of Servants of Mary Elderly Home Inc. in Mohon, Talisay City. A descriptive approach was used to analyze the impact or learning outcomes among the elderly. The study found that the elderly experienced meaningful learning, as evidenced by their strong agreement that they had a holistic learning experience. This was demonstrated through the knowledge they acquired, the development of skills such as listening and sharing with others, as well as the impact on their values and behavior toward others. As a result, their ability to learn through socialization and interaction with different sectors of society was achieved, leading to a greater awareness of their social, mental, physical, emotional, and sensory needs. Therefore, extensive learning was achieved through the extension program Lo ug La: Sugilanon sa Kagahapon, proving its effectiveness in fostering social awareness and environmental impact. Keywords: impact, significance, learning, extension program, storytelling